Prognosis in advanced lung cancer – A prospective study examining key clinicopathological factors. Issue 3 (June 2015) - Simmons, Claribel P.; Koinis, Filippos; Fallon, Marie T.; Fearon, Kenneth C.; Bowden, Jo; Solheim, Tora S.; Gronberg, Bjorn Henning; McMillan, Donald C.; Gioulbasanis, Ioannis; Laird, Barry J.
Highlights Prognostication in advanced lung cancer is difficult due to limits of the TNM classification system. Performance status predicts survival however its subjective nature means it can be inaccurate. A simple inflammation based tool (mGPS) independently predicts survival in advanced lung cancer. The mGPS performs as well as performance status and has the advantage of being objective. The combination of mGPS and performance status improve accuracy of survival prediction.